Legal Safeguards Against Online Child Sexual Exploitation - ZEBIRI, Maria (Journal of Human Sciences, 2025)
The rapid advancement of technology has given rise to the alarming phenomenon of child sexual exploitation online, posing a significant threat to the mental and physical well-being of minors. This situation underscores the urgent need for robust protective measures for children at risk of encountering the pervasive pornographic materials available on the internet, which not only violate moral standards but also represent a profound breach of public decency within society. In light of these challenges, it is imperative to tackle these emerging crimes by enacting laws that criminalize such activities. However, this objective is complicated by the legal intricacies involved in enforcing legislation aimed at combating juvenile sex trafficking. Therefore, to effectively confront this pressing issue, it is essential to strengthen and intensify both national and international initiatives that align with the principles of prevention, control, and public awareness.